How can Business Incubators be Successful? - Staniewicz,Michael; Chattawan,Soravit (2023)
Business incubators facilitate the development of successful startups by providing them with the necessary resources and services. The importance of startups for the economy was highlighted by previous research, individuals could also reflect on how startups have affected their lives by introducing them to new products and services. However, the success rates of startups show that not every new venture was successful which is why business incubators have become more prevalent. They employed different strategies to support startups throughout the years and have to this day remained differentiated to some degree. The reasons for these differences ranged from different forms of ownership of the incubator to the specific needs of certain incubator specializations. This research set out to define the main factors that business incubators need for succeeding and how these differ in the vast amount of literature on this topic. When this was completed, a questionnaire and interview were conducted with managers from business incubators located in different parts of Sweden. The purpose was to investigate which success factors the managers found to be most essential. Combining interviews with a pre-questionnaire allowed this study to first get a clear rating of each success factor where potential biases are minimal, laying the ground for the subsequent interview where the same questions were discussed in-depth. The result of this study showed that business incubator managers viewed incubator manager competence, access to network, and coaching/mentoring hours as the three most essential success factors. Furthermore, these factors were tied to the incubator manager who often had a key role in facilitating them. Although none of the success factors investigated in this study were dismissed as unimportant by the respondents, some got a noticeably lower scores. The location of the incubator and providing shared office space were viewed as the least important out of all the success factors.
Keywords: Business Incubator; Startup; Success Factors; Sweden